Learning ECMAScript 6 : learn all the new ES6 features and be among the most prominent JavaScript developers who can write efficient JS programs as per the latest standards! /: learn all the new ES6 features and be among the most prominent JavaScript developers who can write efficient JS programs as per the latest standards!. (2015) - Prusty, Narayan
No abstract available